Impact of an aryl bulky group on a one-pot reaction of aldehyde with malononitrile and N-substituted 2-cyanoacetamide. Issue 49 (13th September 2019) - Vala, Ruturajsinh M.; Patel, Divyang M.; Sharma, Mayank G.; Patel, Hitendra M.
Abstract : Impact of aryl bulky group on the one-pot reaction of aldehyde with malononitrile and N -substituted 2-cyanoacetamide is examined in the presence of piperidinium acetate as reusable catalyst. Abstract : In this study, we successfully explored the effect of steric hindrance on the one-pot reaction of different aryl aldehydes with malononitrile and N -substituted 2-cyanoacetamide in the presence of piperidinium acetate as the catalyst. It involved the Knoevenagel condensation of the aldehyde and malononitrile to produce arylidene malononitrile as an intermediate, which was further treated with N -substituted 2-cyanoacetamide to give 6-amino-2-pyridone-3, 5-dicarbonitrile derivatives when the less steric bulky group was involved. High steric hindrance changed the earlier reaction route and gave N -substituted 2-cyanoacrylamides via a slower route.